2020
DOI: 10.1016/j.jvssci.2020.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Chemical stabilization of the extracellular matrix attenuates growth of experimentally induced abdominal aorta aneurysms in a large animal model

Abstract: Objective The goal of the present study was to test the safety and efficacy of chemical stabilization of the arterial extracellular matrix as a novel nonoperative treatment of abdominal aortic aneurysms (AAAs) in a clinically relevant large animal model. Methods To achieve matrix stabilization, we used 1,2,3,4,6-pentagalloylglucose (PGG), a noncytotoxic polyphenolic agent capable of binding to and stabilizing elastin and collagen against the action of degrading enzymes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…However, direct periadventitial application would be technically difficult for patients not undergoing an open laparotomy and nearly impossible for patients treated with EVAR. Nonetheless, others have demonstrated PGG’s efficacy using nanoparticle-based approaches in rats [ 11 , 12 ] and surgical intraluminal pressure infusion in pigs and rats [ 15 , 16 , 18 ]. It is difficult to compare the different approaches to PGG delivery, as each method has its own merits and shortcomings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, direct periadventitial application would be technically difficult for patients not undergoing an open laparotomy and nearly impossible for patients treated with EVAR. Nonetheless, others have demonstrated PGG’s efficacy using nanoparticle-based approaches in rats [ 11 , 12 ] and surgical intraluminal pressure infusion in pigs and rats [ 15 , 16 , 18 ]. It is difficult to compare the different approaches to PGG delivery, as each method has its own merits and shortcomings.…”
Section: Discussionmentioning
confidence: 99%
“…This cross-linking of extracellular matrix (ECM) proteins has led to a stabilized arterial microstructure of the abdominal aorta [ 8 ] and partial prevention of mechanical degradation in enzyme-treated arterial tissues [ 9 , 10 ]. Specifically, PGG has been utilized in rat [ 8 , 11 , 12 , 13 ], mice [ 14 ], and porcine [ 15 , 16 ] models of AAA to suppress the pathological expansion. Isenburg et al [ 8 , 17 ] first reported on the periadventitial application of PGG in a rat CaCl 2 model of AAA, which resulted in an overall reduction of arterial dilation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, elastin is not stabilised by glutaraldehyde; therefore, other molecules such as some phytochemicals can similarly or even better improve the physical integrity of protein and polymeric biomaterial. Notably, a large number of polyphenols (e.g., pentagalloyl glucose) are able to enhance the stability as well as the strength of collagen or elastin fibres with different mechanisms [ 87 ]. The tannins, in particular the class of PA, are flavonoids with a great influence on biomechanical properties of both collagen and elastin.…”
Section: New Opportunities For Natural Antioxidant Combination Witmentioning
confidence: 99%